Analisis Tingkat Efisiensi, Efektivitas dan Desentralisasi Fiskal terhadap Kinerja Keuangan Daerah (Studi Kasus pada Kabupaten/Kota di Sumatra Utara) - Haryatmoko Haryatmoko; Swarmilah Hariani (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to analyze the performance of local governments in all districts in Province of North Sumatra for the 2017-2021 budget year. The data used is secondary data obtained from the Audit Board of the Republic of Indonesia in the form of a Budget Realization Report  for the 2017-2021 fiscal year. This study is a descriptive study using an analysis of regional independence ratios and financial ratios to assess the performance of local governments in all districts in Province of North Sumatra. The results showed that the development of the level of efficiency in the management of regional expenditures of all districts in Province of North Sumatra, it can be said less efficient which is the percentage of average yield above 90%.  And then for the development of the level of effectiveness of the management of Regional Original Income, it can be said to be effective, namely with an average yield of above 80%, while for the decentralization of Regional Original Income  is on the low level.